UMPSA hosts the MLBB: ROCT 2023 Grand Championship, boosting the e-sports scene among university students - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PEKAN, 22 November 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), for the first time, played host to the finals of the electronic sports (e-sports) championship, Mobile Legends Bang Bang: Rise of Champions Tournament 2023 (MLBB: ROCT 2023), at the Higher Education Institution (HEI) level.